Analisis Unsur Intrinsik Legenda Situ Bagendit - Wulan Aulia Damayanti; Rodiatul Jannah (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
The legend of Situ Bagendit is one of the Indonesian folktales that is full of moral and cultural values. This research aims to analyze the intrinsic elements in the legend, including themes, characters and characters, plot, setting, point of view, mandate, and symbolism. Using a literary analysis approach, this study reveals how these elements work together to convey a strong moral message. The results of the analysis show that the main theme in the Situ Bagendit Legend is greed and its destructive impact. Nyi Endit, as the main character, represents bad behavior that leads to destruction, while beggars play a role as a symbol of justice and wisdom. The linear storyline and setting where Situ Bagendit reinforces the moral message it contains, namely the importance of sharing, staying away from greed, and living in harmony with others and nature. The message in this story remains relevant in the modern era, making it an effective learning medium to instill social and cultural values. Strong symbolism, such as a beggar's wand and overflowing water, adds depth to the story, giving it a broader dimension to its moral meaning. This study concluded that the Situ Bagendit Legend not only functions as a traditional entertainment, but also as an important cultural heritage to be preserved. Through the analysis of intrinsic elements, this legend can be appreciated as a reflection of noble values that are relevant to the life of today's society.